Strategi Efektif Pengendalian Populasi Hama Kumbang Beras (Sitophilus oryzae L.) dengan Memanfaatkan Serbuk Daun Sirsak (Annona muricata L.) Sebagai Repelen Alami - Rhomadon, Ade Gilang; Arinafil, Arinafil; Ismailsyah Sindapati, Muhammad Isnan; Salsabila, Najwa Fairus; Ramadhani, Nova; Dayfitri, Rafa Anggun; Pratiwi, Dini Putri (Seminar Nasional Lahan Suboptimal, 2024)
Rhomadon, A. G., Arinafril, A., Sindapati, M. I. I, Salsabila N. F., Ramadhani, N., Dayfitri. R A., Pratiwi, D. P. (2024). Effective strategy for controlling rice beetle (Sitophilus oryzae L.) pest poulations by utilizing soursop leaf powder (Annonas muricata L.) as a natural repellent. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembang 21 Oktober 2024. (pp. 690–699).  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Sitophilus oryzae L.is an important pest in warehouses because it can cause significant damage up to 20% and reduce the quality of food security. This study aimed to test the effectiveness of soursop leaf powder as a repellent against S. oryzae L.pests and to develop effective control strategies. The methods used include experimental tests in the Toxicology Laboratory, Plant Protection Study Program, Faculty of Agriculture, Sriwijaya University and sampling at the Storage Warehouse in Indralaya Utara District, Ogan Ilir Regency, South Sumatra Province. The results showed that the highest level of effectiveness was in the S5 treatment using 2.5 grams of soursop leaf powder with a ratio of 10 grams of rice. Each treatment produced a percentage of rejection that was almost different at each test time interval. The percentage of rice beetle rejection will be higher if more soursop leaf powder is used. In conclusion, soursop leaf powder with a dose of 2.5 grams is categorized as quite effective in controlling rice beetle pests (Sitophilus oryzae L.).